2018
DOI: 10.1200/jgo.2017.010082
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Receptor-Defined Breast Cancer Subtypes Between German and Sudanese Women: A Facility-Based Cohort Study

Abstract: PurposeThe objective of this study was to compare tumor characteristics, biomarkers, and surrogate subtypes of breast cancer between Sudanese and German women.MethodsTumor characteristics and immunohistochemistry markers (estrogen receptor [ER], progesterone receptor [PR], and human epidermal growth factor receptor 2 [HER2]) were collected from the routine assessment of consecutive patients with invasive breast cancer diagnosed from 2010 to 2015 (Gezira University Pathology Laboratory, Gezira, Sudan) and from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 42 publications
(69 reference statements)
2
21
3
Order By: Relevance
“…Our data revealed that the average age of the Iraqi patients at the time of diagnosis was 12 years younger than their British counterparts. Similar observations were reported in comparative studies on the characteristics of breast cancer among Saudi versus Swiss women [25], and Sudanese versus German [26] and Italian women [27]. In our study, 43.4% of the British patients were diagnosed after the age of 65 years compared to 6.6% among Iraqis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data revealed that the average age of the Iraqi patients at the time of diagnosis was 12 years younger than their British counterparts. Similar observations were reported in comparative studies on the characteristics of breast cancer among Saudi versus Swiss women [25], and Sudanese versus German [26] and Italian women [27]. In our study, 43.4% of the British patients were diagnosed after the age of 65 years compared to 6.6% among Iraqis.…”
Section: Discussionsupporting
confidence: 91%
“…Cohort studies that compared the clinical and pathological characteristics of breast cancer between Sudanese and German women [26] and between Africans from Central Sudan and Europeans from Northern Italy [27] reported that Sudanese patients were diagnosed at advanced stages exhibiting aggressive breast cancer behavior illustrated in very large tumor sizes and poorly differentiated grades than the German and Italian patients who had significantly lower proportion of positive lymph nodes. A former survey conducted to identify potential molecular differences between breast cancers in Europe and the Middle East demonstrated that the incidence of low-grade disease was 14 times lower in Saudi than Swiss women suggesting differences in genetic susceptibility [25].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that TNBC are the dominant phenotype in native African women [37][38][39][40] and African Americans [5,41,42] compared with white women but in our patients, Luminal A subtype was slightly dominant. The TNBC are considered more common in younger women and associated with aggressive clinicopathologic characteristics [27,38]. Our ndings corroborate with these reports.…”
Section: Discussioncontrasting
confidence: 67%
“…Many studies have reported that TNBC is the dominant phenotype in native African women [ 37 40 ] and African Americans [ 5 , 41 , 42 ] compared with white women. The TNBC is considered more common in younger women and is associated with aggressive clinicopathologic characteristics [ 27 , 38 ]. Our findings corroborate these reports.…”
Section: Discussionmentioning
confidence: 99%